Exploring India's Soft Power Assets: Vasudhaiva Kutumbakam Revisited - Edited by Arvind Gupta; Mitra, Arpita (ed.) (New Delhi Aryan Books International, 2024)
The Vivekananda International Foundation (VIF) has nurtured deliberations on the concept of 'Vasudhaiva Kutumbakam' and its strategic relevance for the world today since 2019. The concept of Vasudhaiva Kutumbakam was the culmination point in a culture$1 (Ba culture that discovered the truth of the oneness of Existence, nurtured it and took it to its logical conclusion in the concept and practice of Vasudhaiva Kutumbakam. In this volume, Vasudhaiva Kutumbakam and similar ideational resources are being highlighted as India's soft power assets. Soft power is the ability of a country to influence other countries and obtain preferred outcomes by attraction and persuasion rather than by coercion or payment.s
Keywords: Vasudhaiva Kutumbakam; Foreign policy and diplomacy; IFS as an editor